PENINGKATAN TEKANAN DARAH PADA USIA 60-70 TAHUN DI DAERAH PANTAI PUGER KABUPATEN JEMBER - Suhartini, Suhartini (FKM - UNEJ, 2007)
At present, the problem of old-aged is increasing the proportion of old-aged, especially in Indonesia. So, the health maintenance of old-aged are important. The goal of this research is to know the increase of blood pressure in old-aged. Research typed used is abservational analytic. The data cames from blood pressure of 64 old-aged from simple random sampling Â in Pugerâs beach and the quisionerâs answer.The research is result of the research show that the blood pressure of old-aged is 130/81 mmHg for women old-aged and 132/81 mmHg for men old-aged. So, the conclusion of this research is increasing blood pressure of old-aged in Pugerâs beach is not happen. The causes is consumption of balance food between fish, vegetables and fruits.Â Key words: blood pressure, old-aged, beach